# Question-68305

Question Number 68305 by TawaTawa last updated on 08/Sep/19
Commented by ajfour last updated on 10/Sep/19
Commented by ajfour last updated on 10/Sep/19
$${Area}\:\:{S}_{{req}} =\underset{\smile} {{GC}E}\:\:\:\: \\$$$$\left({image}\:{distorted}\:{purposely}\right. \\$$$${so}\:{that}\:{area}\:{BCG}\:{is}\:{to}\:{be} \\$$$$\left.\:{enlarged}\right). \\$$$${consider}\:{A}\:{to}\:{be}\:{center}\:{of} \\$$$${semicircle}. \\$$$${S}_{\mathrm{1}} ={sector}\:{area}\:{A}\overset{\frown} {{CE}} \\$$$${S}_{\mathrm{2}} =\:{area}\left(\bigtriangleup{ABE}\right) \\$$$${S}_{\mathrm{3}} =\:{area}\left(\bigtriangleup{BCD}\right) \\$$$${S}_{\mathrm{4}} =\:{sector}\:{area}\:{D}\overset{\frown} {{GC}} \\$$$${S}_{{req}} ={S}_{\mathrm{1}} −{S}_{\mathrm{2}} +{S}_{\mathrm{3}} −{S}_{\mathrm{4}} \\$$$${C}\left(\frac{\mathrm{2}}{\mathrm{5}},\frac{\mathrm{4}}{\mathrm{5}}\right)\:\:\:;\:{E}\left(\frac{\mathrm{1}}{\mathrm{2}},\frac{\mathrm{1}}{\mathrm{2}}\right)\:; \\$$$${G}\left(\frac{\mathrm{2}−\sqrt{\mathrm{6}}}{\mathrm{2}},\:\frac{\sqrt{\mathrm{6}}}{\mathrm{2}}\right)\:\:;\:\:{B}\left(\frac{\mathrm{2}}{\mathrm{7}},\frac{\mathrm{5}}{\mathrm{7}}\right) \\$$$${S}_{\mathrm{1}} =\frac{{r}^{\mathrm{2}} \theta}{\mathrm{2}}\:\:\:{with}\:{r}=\frac{\mathrm{1}}{\mathrm{2}}\:,\:\theta=\mathrm{cos}^{−\mathrm{1}} \frac{\mathrm{4}}{\mathrm{5}} \\$$$$\Rightarrow\:\:\:\:{S}_{\mathrm{1}} =\frac{\mathrm{1}}{\mathrm{8}}\mathrm{sin}^{−\mathrm{1}} \frac{\mathrm{3}}{\mathrm{5}} \\$$$${S}_{\mathrm{2}} =\frac{\mathrm{1}}{\mathrm{2}}{r}\left({y}_{{B}} −{r}\right)=\frac{\mathrm{1}}{\mathrm{4}}\left(\frac{\mathrm{5}}{\mathrm{7}}−\frac{\mathrm{1}}{\mathrm{2}}\right)=\frac{\mathrm{3}}{\mathrm{56}} \\$$$${S}_{\mathrm{3}} =\frac{\mathrm{1}}{\mathrm{2}}\begin{vmatrix}{\mathrm{1}}&{\mathrm{0}}&{\mathrm{1}}\\{\mathrm{2}/\mathrm{5}}&{\mathrm{4}/\mathrm{5}}&{\mathrm{1}}\\{\mathrm{2}/\mathrm{7}}&{\mathrm{5}/\mathrm{7}}&{\mathrm{1}}\end{vmatrix} \\$$$$\:\:\:=\left(\frac{\mathrm{4}}{\mathrm{5}}−\frac{\mathrm{5}}{\mathrm{7}}\right)+\left(\frac{\mathrm{2}}{\mathrm{7}}−\frac{\mathrm{8}}{\mathrm{35}}\right)=\frac{\mathrm{28}−\mathrm{25}+\mathrm{10}−\mathrm{8}}{\mathrm{35}} \\$$$$\:\:=\frac{\mathrm{1}}{\mathrm{7}} \\$$$${S}_{\mathrm{4}} =\frac{{R}^{\mathrm{2}} \phi}{\mathrm{2}}\:\:{with}\:{R}=\mathrm{1}\: \\$$$${and}\:\phi=\mathrm{sin}^{−\mathrm{1}} \left({y}_{{C}} \right)−\frac{\pi}{\mathrm{4}} \\$$$$\:\:\:\Rightarrow\:\:{S}_{\mathrm{4}} =\frac{\mathrm{1}}{\mathrm{2}}\mathrm{sin}^{−\mathrm{1}} \frac{\mathrm{4}}{\mathrm{5}}−\frac{\pi}{\mathrm{8}} \\$$$${S}_{{req}} =\frac{\mathrm{1}}{\mathrm{8}}\mathrm{sin}^{−\mathrm{1}} \frac{\mathrm{3}}{\mathrm{5}}−\frac{\mathrm{3}}{\mathrm{56}}+\frac{\mathrm{1}}{\mathrm{7}}−\frac{\mathrm{1}}{\mathrm{2}}\mathrm{sin}^{−\mathrm{1}} \frac{\mathrm{4}}{\mathrm{5}}+\frac{\pi}{\mathrm{8}}\:. \\$$
Commented by TawaTawa last updated on 10/Sep/19
$$\mathrm{Wow},\:\mathrm{God}\:\mathrm{bless}\:\mathrm{you}\:\mathrm{sir}. \\$$
Answered by mr W last updated on 08/Sep/19
$${let}\:{side}\:{length}\:{of}\:{square}=\mathrm{1} \\$$$${take}\:{A}\:{as}\:{origin}\:{and}\:{AD}\:{as}\:{x}−{axis}. \\$$$${eqn}.\:{of}\:{big}\:{circle}: \\$$$$\left({x}−\mathrm{1}\right)^{\mathrm{2}} +{y}^{\mathrm{2}} =\mathrm{1} \\$$$${eqn}.\:{of}\:{small}\:{circle}: \\$$$${x}^{\mathrm{2}} +\left({y}−\frac{\mathrm{1}}{\mathrm{2}}\right)^{\mathrm{2}} =\frac{\mathrm{1}}{\mathrm{4}} \\$$$${eqn}.\:{of}\:{line}\:{BD}: \\$$$${y}=\mathrm{1}−{x} \\$$$$\\$$$${intersection}\:{of}\:{big}\:{and}\:{small}\:{circles}: \\$$$$\left({x}−\mathrm{1}\right)^{\mathrm{2}} +{y}^{\mathrm{2}} =\mathrm{1}\:\:\:\:…\left({i}\right) \\$$$${x}^{\mathrm{2}} +\left({y}−\frac{\mathrm{1}}{\mathrm{2}}\right)^{\mathrm{2}} =\frac{\mathrm{1}}{\mathrm{4}}\:\:\:…\left({ii}\right) \\$$$$\left({i}\right)−\left({ii}\right): \\$$$$\Rightarrow{y}=\mathrm{2}{x} \\$$$$\left({x}−\mathrm{1}\right)^{\mathrm{2}} +\mathrm{4}{x}^{\mathrm{2}} =\mathrm{1} \\$$$$\mathrm{5}{x}^{\mathrm{2}} −\mathrm{2}{x}+\mathrm{1}=\mathrm{1} \\$$$${x}\left(\mathrm{5}{x}−\mathrm{2}\right)=\mathrm{0} \\$$$$\Rightarrow{x}=\mathrm{0}\:{or}\:{x}=\frac{\mathrm{2}}{\mathrm{5}} \\$$$${intersection}\:{of}\:{big}\:{circle}\:{and}\:{BD}: \\$$$$\left({x}−\mathrm{1}\right)^{\mathrm{2}} +\left(\mathrm{1}−{x}\right)^{\mathrm{2}} =\mathrm{1}\:\:\: \\$$$${x}^{\mathrm{2}} −\mathrm{2}{x}−\frac{\mathrm{1}}{\mathrm{2}}=\mathrm{0} \\$$$$\Rightarrow{x}=\mathrm{1}−\sqrt{\mathrm{1}+\frac{\mathrm{1}}{\mathrm{2}}}=\frac{\mathrm{2}−\sqrt{\mathrm{6}}}{\mathrm{2}} \\$$$${intersection}\:{of}\:{small}\:{circle}\:{and}\:{BD}: \\$$$${x}^{\mathrm{2}} +\left(\frac{\mathrm{1}}{\mathrm{2}}−{x}\right)^{\mathrm{2}} =\frac{\mathrm{1}}{\mathrm{4}}\: \\$$$${x}\left(\mathrm{2}{x}−\mathrm{1}\right)=\mathrm{0} \\$$$$\Rightarrow{x}=\mathrm{0}\:{or}\:{x}=\frac{\mathrm{1}}{\mathrm{2}} \\$$$${big}\:{circle}: \\$$$$\Rightarrow{y}=\sqrt{{x}\left(\mathrm{2}−{x}\right)} \\$$$${small}\:{circle}: \\$$$${y}=\frac{\mathrm{1}}{\mathrm{2}}+\sqrt{\frac{\mathrm{1}}{\mathrm{4}}−{x}^{\mathrm{2}} } \\$$$$\\$$$${shaded}\:{area}: \\$$$${A}=\int_{\frac{\mathrm{2}−\sqrt{\mathrm{6}}}{\mathrm{2}}} ^{\frac{\mathrm{2}}{\mathrm{5}}} \left[\sqrt{{x}\left(\mathrm{2}−{x}\right)}−\mathrm{1}+{x}\right]{dx}+\int_{\frac{\mathrm{2}}{\mathrm{5}}} ^{\frac{\mathrm{1}}{\mathrm{2}}} \left[\frac{\mathrm{1}}{\mathrm{2}}+\sqrt{\frac{\mathrm{1}}{\mathrm{4}}−{x}^{\mathrm{2}} }−\mathrm{1}+{x}\right]{dx} \\$$$${A}=\int_{\frac{\mathrm{2}−\sqrt{\mathrm{6}}}{\mathrm{2}}} ^{\frac{\mathrm{2}}{\mathrm{5}}} \left[\sqrt{{x}\left(\mathrm{2}−{x}\right)}−\mathrm{1}+{x}\right]{dx}+\int_{\frac{\mathrm{2}}{\mathrm{5}}} ^{\frac{\mathrm{1}}{\mathrm{2}}} \left[\sqrt{\frac{\mathrm{1}}{\mathrm{4}}−{x}^{\mathrm{2}} }−\frac{\mathrm{1}}{\mathrm{2}}+{x}\right]{dx} \\$$$${A}=\left[\frac{\left({x}−\mathrm{1}\right)\sqrt{{x}\left(\mathrm{2}−{x}\right)}+\mathrm{sin}^{−\mathrm{1}} \left({x}−\mathrm{1}\right)}{\mathrm{2}}−{x}+\frac{{x}^{\mathrm{2}} }{\mathrm{2}}\right]_{\frac{\mathrm{2}−\sqrt{\mathrm{6}}}{\mathrm{2}}} ^{\frac{\mathrm{2}}{\mathrm{5}}} +\left[\frac{\mathrm{sin}^{−\mathrm{1}} \left(\mathrm{2}{x}\right)}{\mathrm{8}}+\frac{{x}\sqrt{\frac{\mathrm{1}}{\mathrm{4}}−{x}^{\mathrm{2}} }}{\mathrm{2}}−\frac{{x}}{\mathrm{2}}+\frac{{x}^{\mathrm{2}} }{\mathrm{2}}\right]_{\frac{\mathrm{2}}{\mathrm{5}}} ^{\frac{\mathrm{1}}{\mathrm{2}}} \\$$$$…… \\$$
Commented by TawaTawa last updated on 08/Sep/19
$$\mathrm{Wow},\:\mathrm{thanks}\:\mathrm{for}\:\mathrm{your}\:\mathrm{time}\:\mathrm{sir}.\:\:\mathrm{God}\:\mathrm{bless}\:\mathrm{you}. \\$$$$\mathrm{Waiting}\:\mathrm{for}\:\mathrm{the}\:\mathrm{rest}\:\mathrm{sir} \\$$
Commented by TawaTawa last updated on 10/Sep/19
$$\mathrm{This}\:\mathrm{area}\:\mathrm{is}\:\mathrm{too}\:\mathrm{tough}.\:\mathrm{The}\:\mathrm{integration}\:\mathrm{formed}\:\mathrm{is}\:\mathrm{complex}. \\$$